2016
DOI: 10.18632/oncotarget.6942
|View full text |Cite
|
Sign up to set email alerts
|

BRAF associated autophagy exploitation: BRAF and autophagy inhibitors synergise to efficiently overcome resistance of BRAF mutant colorectal cancer cells

Abstract: Autophagy is the basic catabolic mechanism that involves cell degradation of unnecessary or dysfunctional cellular components. Autophagy has a controversial role in cancer – both in protecting against tumor progression by isolation of damaged organelles, or by potentially contributing to cancer growth. The impact of autophagy in RAS induced transformation still remains to be further analyzed based on the differential effect of RAS isoforms and tumor cell context. In the present study, the effect of KRAS/BRAF/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 66 publications
3
52
0
Order By: Relevance
“…One previous study 46 has reported that tumor SQSTM1 expression is not associated with tumor location, but the sample size was much smaller (n D 178) than our current study. In an in vitro experimental study, 61 KRAS mutation in colorectal cancer appeared to attenuate tumor SQSTM1 expression level, and we observed the similar trend. In another in vitro experimental study, 62 F. nucleatum appeared to induce impairment of autophagic activity of host cells; however, our current data do not support such negative effects of F. nucleatum on autophagic activity of tumor cells.…”
Section: Discussionsupporting
confidence: 77%
“…One previous study 46 has reported that tumor SQSTM1 expression is not associated with tumor location, but the sample size was much smaller (n D 178) than our current study. In an in vitro experimental study, 61 KRAS mutation in colorectal cancer appeared to attenuate tumor SQSTM1 expression level, and we observed the similar trend. In another in vitro experimental study, 62 F. nucleatum appeared to induce impairment of autophagic activity of host cells; however, our current data do not support such negative effects of F. nucleatum on autophagic activity of tumor cells.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, Goulielmaki and colleagues reported that PI3K/AKT/MTOR inhibitors induce autophagic tumor properties, whereas RAF/MEK/ERK signaling inhibitors reduce expression of autophagic markers. They showed that pre-treatment of autophagy inhibitor 3-MA followed by its combination with BRAFV600E targeting drug PLX4720 can synergistically sensitize resistant colorectal tumors [129].…”
Section: Additional Mechanismsmentioning
confidence: 99%
“…After 72 h of exposure to drug, cell viability was assessed by the MTS assay. Viability curves like those shown in Figure 2A were fit to an inhibition model to determine the IC 50 . As summarized in Figure 2B, and detailed in Table 1, CMQ exhibited more greater potency than CQ across all cell lines tested, as indicated by lower pairwise IC 50 values in both normal and low pH settings.…”
Section: Cmq Exhibits Greater Potency Than Cq In Both Normal and Lomentioning
confidence: 99%